International mechanisms for the protection of human rights and democratic values: case of Belarus - Mazure, Monta Amanta (Riga Graduate School of Law, 2022)
In August 2020, the world learned about the misconduct of the Belarus presidential elections, which entailed numerous grave violations to human rights and democratic values of the civil society of Belarus. Promotion and the protection of human rights is one of the most important parts of international law, thus, there was an immediate international response. The thesis focuses on international human rights enforcement mechanisms in relation to the case of Belarus. The thesis is to provide an in-depth understanding of violations associated with Belarus elections and with that in mind, the objective of the thesis is to identify enforcement mechanisms of the United Nations and European Union, and analyze how the identified human rights mechanisms are implemented towards the situation in Belarus.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Human rights; Belarus presidential elections 2020; The Republic of Belarus